Efficiency Enhancement in Photovoltaic Devices Using Light Management and Morphology - Kumalo, Sandile (University of the Witwatersrand, Johannesburg, 2024)
Meeting the ever-increasing global demand for energy is society’s principal challenge for attaining economic growth and dynamic technological progress. Novel materials and technologies to extend photoabsorption and harness the solar emission spectrum are critical for producing solar-based electricity on a large scale. Current techniques and nanostructure-based approaches can revolutionise the production of solar electricity. In this work, experimental light management strategies through plasmonic nanostructures in silicon-based thin film solar cells were explored to augment power conversion efficiency (PCE). These devices incorporated plasmonic, magnetoplasmonic, and coreshell nanostructures coated with SiO2. It was demonstrated that magnetoplasmonic nanoparticles enhance interactions with both the charge of electrons and the unpaired spin with the B-field component of the electromagnetic spectrum. Furthermore, core-shell structures passivate the surface of the nanoparticles, significantly enhancing PCE. The highest PCE (10.7%) was observed for Au@SiO2 nanoparticles, attributed to a bonding plasmon mode at the interface between the nanoparticles and the surrounding bulk material. Additionally, F e3O4@SiO2 nanoparticles primarily enhanced the short-circuit current (Jsc), due to magnetic interactions with superparamagnetic nanoparticles. A detailed investigation into the Curie temperature (Tc) of various magnetic nanoparticles revealed that 4 nm F e3O4 nanoparticles possess the highest Tc of 906.1 K, indicating strong magnetic stability under operational conditions. For Ni@Fe core-shell nanoparticles, a decrease in Tc with increasing Ni content was observed, highlighting the critical role of composition in tuning magnetic properties. Morphological analysis through TEM imaging revealed uniform dispersion and spherical morphology for Au nanoparticles, crucial for consistent plasmonic properties. The addition of SiO2 shells to both Au and Ag nanoparticles significantly improved their optical absorption characteristics due to the modification of the local dielectric environment. Furthermore, a study on the bulk heterojunction of organic solar cells demonstrated that processing solvents play a pivotal role in optimising active layer performance. It was found that solvent mixtures, particularly 2-MEA and toluene in a 7:3 ratio, significantly enhance device efficiency by promoting better phase separation and charge transport, achieving a PCE of 5.77%. These findings showcase the significant potential of nanostructures and solvent processing in improving the efficiency of photovoltaic devices. The enhanced PCE and stability of devices incorporating plasmonic and magnetoplasmonic nanoparticles, along with optimised solvent processing techniques, provide valuable insights for future research and development in solar energy technologies.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Physics, .to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2024
Keywords: Photovoltaic; Plasmonic; Magnetoplasmonic; Devices; Organic Solar Cells; Power Conversion Efficiency; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-4: Quality education